THE EFFECT OF AUTOGENIC RELAXATION ON PAIN RELIEF IN HYPERTENSION PATIENTS: A SYSTEMATIC REVIEW - Listari, Risti Puji; Sulistyowati, Agus; Wijayanti, Dini Prastyo (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Hypertension can be treated with non-pharmacological treatment. Comprehensive chronic pain treatment involves a combination of methods and therapies. Relaxation effectively reduces muscle tension, improves well-being, and reduces symptomatic stress in individuals experiencing various situations. Autogenic relaxation therapy carried out for ± 10 minutes scientifically has a physiological impact on the body. Objective: This literature review aimed to identify the effect of autogenic relaxation on pain reduction in hypertensive patients Design: This research design was a literature review. Data Sources: Search for articles using three journal databases, namely Google Scholar, PubMed, and ScienceDirect. Reviews Methods: Used PRISM flow diagram to find a total of 6 articles that meet the inclusion criteria reviewed. Result: The literature search results found 2 articles that met the inclusion criteria that were published in 2023. Conclusion: One of types of relaxation is an autogenic relaxation on reducing pain in hypertensive patients. Continue to do relaxation routinely and regularly both independently and with guidance from experts, and continue to take medication according to doctor's recommendations and carry out routine checks with doctors, for symptom improvement.